Advancements in Network Infrastructure for Large-Scale Educational and Industrial Systems - Prasanth Kosaraju, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the evolution of network infrastructures supporting large-scale educational and industrial environments facing increasing demands for reliability, performance, and security. Through a comprehensive analysis of standardized architectures, hybrid cloud integrations, and advanced monitoring frameworks, the article explores how modern network designs address complex operational challenges. Standardized approaches incorporating stakeholder feedback and systems thinking methodologies enable consistent deployments across distributed environments while maintaining flexibility for local requirements. The integration of software-defined networking capabilities transforms provisioning, traffic optimization, and security segmentation, creating adaptable infrastructures responsive to changing operational needs. AI-driven monitoring frameworks shift organizations from reactive to proactive postures through anomaly detection, automated compliance validation, and real-time telemetry. Zero-trust security models fundamentally transform protection strategies through micro-segmentation, continuous authorization, and comprehensive encryption. The transformation roadmap addresses legacy integration challenges while positioning organizations for emerging edge computing paradigms and sustainability imperatives.
Keywords: Network architecture; Zero-trust security; AI-driven monitoring; Edge computing; Digital transformation